‘It’s far too complicated’: why fragmentation persists in global health - Spicer, Neil; Agyepong, Irene; Ottersen, Trygye; Jahn, Albrecht; Ooms, Gorik (Globalization and health, 2020)
Despite many efforts to achieve better coordination, fragmentation is an enduring feature of the global health landscape that undermines the effectiveness of health programmes and threatens the attainment of the health-related Sustainable Development Goals. In this paper we identify and describe the multiple causes of fragmentation in development assistant for health at the global level. The study is of particular relevance since the emergence of new global health problems such as COVID-19 heightens the need for global health actors to work in coordinated ways. Our study is part of the Lancet Commission on Synergies between Universal Health Coverage, Health Security and Health Promotion.